1986
DOI: 10.1128/jb.168.3.1358-1365.1986
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic adjustment in the filamentous fungus Aspergillus nidulans

Abstract: Aspergillus nidulans was shown to be xerotolerant, with optimal radial growth on basal medium amended with 0.5 M NaCl (osmotic potential [*,] of medium, -3 MPa), 50% optimal growth on medium amended with 1.6 M NaCl (*s of medium, -8.7 MPa), and little growth on medium amended with 3.4 M NaCl (*, of medium, -21 MPa). The intracellular content of soluble carbohydrates and of selected cations was measured after growth on basal medium, on this medium osmotically amended with NaCl, KCI, glucose, or glycerol, and al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
57
1
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(66 citation statements)
references
References 23 publications
7
57
1
1
Order By: Relevance
“…(Kim et al, 1997). All four polyols have been detected in some Aspergillus species (Beever & Laracy, 1986;Nesci et al, 2004) and in C. sake (Abadias et al, 2000). In addition to their use as compatible solutes, polyols can also serve as carbon storage compounds, they may help in balancing the cellular redox potential (Diano et al, 2006), and they can act as scavengers of reactive oxygen species (Voegele et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…(Kim et al, 1997). All four polyols have been detected in some Aspergillus species (Beever & Laracy, 1986;Nesci et al, 2004) and in C. sake (Abadias et al, 2000). In addition to their use as compatible solutes, polyols can also serve as carbon storage compounds, they may help in balancing the cellular redox potential (Diano et al, 2006), and they can act as scavengers of reactive oxygen species (Voegele et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, high internal and external concentrations of arabitol and erythritol (Table 3) were found in the creAd-30 strain, and these high internal concentrations may have some toxic effect in the creAd-30 strain resulting in, for instance, compact growth. Because of the role polyols have in maintaining the osmotic balance (Beever & Laracy, 1986;Van Laere, 1989), it is likely that the total internal concentration of these polyols remains constant for a given set of growth conditions. Polyols which are overproduced are therefore likely to be secreted, as was found with the creAd-30 mutant, which had high extracellular levels of all polyols although the total internal polyol concentration was almost the same as that in the wild-type (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…38 In M. oryzae, it has been shown that turgor in the appressorium is a consequence of the accumulation of huge quantities of glycerol in a central vacuole of the cell. 21 Formation of a central vacuole filled with glycerol is not observed in M. oryzae mutants deleted for one of the MoATG2, MoATG4, MoATG5, MoATG9 or MoATG18 genes.…”
Section: Infection Structures Of Pathogenic Fungimentioning
confidence: 99%